2014
DOI: 10.1074/jbc.m114.563734
|View full text |Cite
|
Sign up to set email alerts
|

N-Glycan Remodeling on Glucagon Receptor Is an Effector of Nutrient Sensing by the Hexosamine Biosynthesis Pathway

Abstract: Background:The hexosamine biosynthesis pathway to UDP-GlcNAc has been implicated in glucose homeostasis. Results: UDP-GlcNAc and Golgi N-acetylglucosaminyltransferases modify the N-glycans on glucagon receptor, which increases sensitivity to glucagon in vivo. Conclusion: The hexosamine biosynthesis pathway contributes to glucose homeostasis, in part through N-glycan branching on glucagon receptor. Significance: Hepatic Mgat5 and the N-glycan branching pathway may be a therapeutic target for control of glycemia. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 67 publications
3
49
0
Order By: Relevance
“…7C), consistent with a previous report that the ERK pathway is activated in Apc min/ϩ mice (63). The function of various cell surface receptors has been shown to be modulated by GnT-V and this modulation often causes aberrant downstream signaling mediated by these receptors (14,15,17,64). The binding of the Wnt ligand to Wnt receptors triggers canonical Wnt signaling, leading to downstream Wnt-target gene expression (52).…”
Section: Discussionsupporting
confidence: 77%
“…7C), consistent with a previous report that the ERK pathway is activated in Apc min/ϩ mice (63). The function of various cell surface receptors has been shown to be modulated by GnT-V and this modulation often causes aberrant downstream signaling mediated by these receptors (14,15,17,64). The binding of the Wnt ligand to Wnt receptors triggers canonical Wnt signaling, leading to downstream Wnt-target gene expression (52).…”
Section: Discussionsupporting
confidence: 77%
“…A possible explanation for this higher branching might be that higher glycaemia leads to altered flux through the hexosamine pathway, which produces uridine diphosphate-Nacetylglucosamine, the substrate for N-linked glycosylation [16]. Recently, it has also been shown that the hexosamine biosynthesis and N-acetylglucosamine salvage pathways contribute to glucose homeostasis through N-glycan branching on the glucagon receptor [17].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the presence of Mgat5-induced branched N-glycans on the glucagon receptor (GCGR) promotes crosslinking by Gal9, which reduces its lateral mobility and increases responsiveness to glucagon in hepatocytes. Mgat5 expression and UDP-GlcNAc availability cooperate to form a positive-feedback loop that further increases the responsiveness of the receptor to glucagon (Johswich et al, 2014). In cultured HEK293 epithelial cells, inducible expression of Mgat5 has been shown to promote glutamine transport and to rescue cell growth under conditions of low nutrient availability (Abdel Rahman et al, 2015).…”
Section: Metabolismmentioning
confidence: 99%
“…Furthermore, because a high degree of membrane remodeling occurs in proliferating cells, macrophage and tumor cells, there is greater demand on the lattice in these cells in order to support the appropriate surface retention of receptors and transporters. TGFβRII , cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) (Mkhikian et al, 2011) and glucagon receptor (Johswich et al, 2014) Therefore, both genetic inputs, such as the number of NxS/T sites and trafficking motifs, as well as metabolic cues (the availability of UDP-GlcNAc) control the association of receptors with the galectin lattice (see poster).…”
Section: Regulation Of Receptor Kinases By the Galectin Latticementioning
confidence: 99%
See 1 more Smart Citation